Examining Jakarta office mosques: Islamic teaching practices and views of Islamic ideological issues - Al-Makassary, Ridwan (Indonesian Journal of Islam and Muslim Societies, 2013)
This paper discusses Islamic teaching practices and perceptions of mosque stake-holders concerning the ideological issues of: a democratic system of governmentversus formal implementation of Islamic sharia; gender equality; jihad, and plu-ralism in the Jakarta office mosques. After describing the research findings, thepaper concludes that the phenomenon of neo-fundamentalism (in Olivier Royâswords) is growing and developing in office mosques. This can be seen in thedominance of literal and scripturalist Islamic interpretations, the importance givento implementing Islamic sharia and the rejection of democracy, a hatred of Jewsand Christians and the emergence of Muslim youth actors in Islamic neo-fundamentalism. Other findings concern the influence of the Tarbiyah movement, anoffshoot of the Ikhwanul Muslimin (Muslim Brotherhood), which is being felt inthe office mosques studied. Learning about Islamist understandings will allow usto check its development, which may destroy the friendly, peaceful face of Islam.PaperÂ  iniÂ  mendiskusikanÂ  praktikÂ  pengajaranÂ  IslamÂ  danÂ  persepsiÂ  pemangkukepentinganÂ  masjidÂ  berkaitanÂ  denganÂ  isu-isuÂ  ideologis:Â  sebuahÂ  sistempemerintahan demokratik versus implementasi formal syariâat Islam; kesetaraanjender; jihad, dan pluralism di masjid perkantoran Jakarta. Setelah deskripsitemuanÂ  penelitian,Â  paperÂ  iniÂ  menyimpulkanÂ  bahwaÂ  fenomenaÂ  neo-fundamentalisme (meminjam Olivier Roy) sedang tumbuh dan berkembang dimasjid-masjid perkantoran. Ini terlihat dari dominannya intepretasi skripturaldan literal, pentingnya menerima pelaksanaan formal syariâat Islam, kebencianterhadap Yahudi dan Kristen dan kebangkitan aktor-aktor muda fundamentalismeIslam. Temuan lain terkait dengan gerakan Tarbiyah, sebuah anak ideologi IkhwanulMuslimin (Muslim Brotherhood), yang cukup kental ditemukan di masjid yangditeliti.Â  MengkajiÂ  pemahamanÂ  IslamÂ  akanÂ  memungkinkanÂ  kitaÂ  mengawasiperkembangannya, yang mungkin menghancurkan wajah Islam yang ramah dandamai.